2020
DOI: 10.1021/acsnano.9b08421
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating an Ensemble of Chemical Micromotors via Spontaneous Synchronization

Abstract: Spatiotemporal coordination of a nanorobot ensemble is critical for their operation in complex environments, such as tissue removal or drug delivery. Current strategies of achieving this task, however, rely heavily on sophisticated, external manipulation. We here present an alternative, biomimetic strategy by which oscillating Ag Janus micromotors spontaneously synchronize their dynamics as chemically coupled oscillators. By quantitatively tracking the kinetics at both an individual and cluster level, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 61 publications
0
46
0
Order By: Relevance
“…Consequently, a slowdown of propulsion may result from fuel exhaustion or decomposition. More complicated modifications, like oscillatory propulsion, on-off switches, steering, cargo pickup and delivery, are conveniently realized employing oscillating chemical reactions [35,36], as well as via additional local or global magnetic or optical fields [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a slowdown of propulsion may result from fuel exhaustion or decomposition. More complicated modifications, like oscillatory propulsion, on-off switches, steering, cargo pickup and delivery, are conveniently realized employing oscillating chemical reactions [35,36], as well as via additional local or global magnetic or optical fields [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…These are further increased in the case of collective behaviour like swarm formation and other dynamic phase transitions [32]. Several diffusio-phoretic selfpropulsion mechanisms and the corresponding swimming performance have been characterized in great detail [24][25][26][27][28][29][30][31][34][35][36][37][38][39][40][41]. However, experimental data on the shape and evolution of the relevant chemical concentration fields, as well as on their mutual phoretic and hydrodynamic couplings, are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the nonoscillatory micromotors can be transformed into spontaneous oscillators after the diffusion and deposition of Ag ions, which shows an intelligent “teaching and learning” behavior and the possibility of smart LMNR design (Figure 7c). [ 96–99 ]…”
Section: Assembly and Swarming Behaviors Of Lmnr Systemsmentioning
confidence: 99%
“…Interestingly, the nonoscillatory micromotors can be transformed into spontaneous oscillators after the diffusion and deposition of Ag ions, which shows an intelligent "teaching and learning" behavior and the possibility of smart LMNR design (Figure 7c). [96][97][98][99] An artificial active system can be achieved by the lighttriggered assembly. Palacci et al have, for instance, demonstrated a crystal formation in photoactivated Fe 2 O 3 -polymer sphere (3-methacryloxypropyl trimethoxysilane) patchy particles, which were referred to as "living crystals", and showed reversible crystallization and disassembly manipulated by light.…”
Section: Photochemical-reaction Related Assembly and Swarming Of Lmnr Systemsmentioning
confidence: 99%
“…Biomimetic control Ref. [ 165] Chemically powered oscillatory micromotors that spontaneously synchronize Termination Safe, biocompatible removal of nanomotors Designing nanomotors with biodegradable materials…”
Section: Operationmentioning
confidence: 99%